Perceived Family and Friend Support Moderate Pathways From Peer Victimization to Substance Use in Early-Adolescent Girls and Boys: A Moderated-Mediation Analysis. (January 2021) - Vannucci, Anna; Fagle, Tessa R.; Simpson, Emily G.; Ohannessian, Christine McCauley
This study examined gender differences in a moderated-mediation model examining whether perceived social support moderated depressive symptom and academic achievement mediation pathways from peer victimization to substance use among 1, 334 U.S. early adolescents (11-14 years, 50% girls, 51% White). Surveys were administered in schools at three 6-month intervals. Multiple group analyses suggested that the moderated-mediation model differed for boys and girls. Indirect effects suggested that declines in academic achievement mediated the relationship between peer victimization and substance use for girls and boys, while elevated depressive symptoms mediated this relationship for girls only. Higher family and friend support attenuated the relationship between overt victimization and academic achievement for boys and between relational victimization and depressive symptoms for girls. These findings implicate two risk pathways that account for why peer victimization enhances substance use risk and emphasize the importance of perceived support following peer victimization during early adolescence. Gender differences require replication.